Optimal Operation Analysis of the Distribution Network Comprising a Micro Energy Grid Based on an Improved Grey Wolf Optimization Algorithm - Xin Zhang; Jianhua Yang; Weizhou Wang; Tianjun Jing; Man Zhang (Applied Sciences, 2018)
With a focus on the safe, stable, and economical operation of a micro energy grid and a distribution network, this study proposes a bi-level optimal model for the integrated operation of a micro energy grid and a distribution network. The upper model used the minima of three objectives, including the integrated operating cost of the distribution network, the network’s active power loss, and the standard deviation of the voltage deviation in the distribution network. The lower model used the minimum integrated operating cost for the micro energy grid as the objective function. Considering the large number of objectives in the upper model, and that no single optimal solution existed, the judgment-matrix method was used to obtain the weight factors of each objective, and the upper multi-objective optimization problem was transformed into a single-objective problem in this paper. A grey wolf optimization algorithm based on the dynamic adjustment of the proportional weight and convergence factor was proposed to solve the operating model of the distribution network comprising the micro energy grid. This algorithm offers a high solution precision, a high convergence speed, and a strong global searching ability. The nonlinear convergent factor formula proposed in this paper dynamically adjusted the global searching ability of the algorithm, while the proposed proportional weight sped up the convergence of the algorithm. The superiority of the proposed algorithm was verified mathematically by six test functions. The simulation results demonstrated that the model and algorithm proposed in this paper improved the economic benefits, and voltage stability of the distribution network, reduced the active power loss of the distribution network, and enabled the safe, stable, and economical operation of the distribution network comprising a micro energy grid.